Enhancing Safety in Nigeria's Oil and Gas Sector: A Fault Tree Analysis Approach - Mgbowaji Zacchaeus; John Nwenearizi Ugbebor; Ikechukwu Ozoemenam Agbagwa; Ochuko Felix Orikpete (The Journal of Engineering and Exact Sciences)
The oil and gas industry, a cornerstone of the global energy supply, faces multifaceted challenges that threaten its operational integrity, environmental sustainability, and socio-economic contributions, particularly in regions like Nigeria where the sector's growth is pivotal to national development. This study embarks on a critical examination of safety and risk management in Nigeria's oil and gas sector, employing Fault Tree Analysis (FTA) to navigate the intricate web of operational hazards that compromise its safety and efficiency. By dissecting incidents ranging from structural failures to security threats, the research illuminates the multifaceted risks entrenched within the sector's activities. Through the lens of FTA, we not only identify specific vulnerabilities but also propose targeted mitigation strategies, thereby contributing valuable insights towards enhancing safety protocols. This investigation, rooted in the Nigerian oil and gas industry, underscores the broader applicability of FTA in addressing complex safety challenges in similar operational contexts globally. Furthermore, the study's emphasis on the sector's exposure to security risks and natural calamities calls for an integrated safety and risk management strategy. By proposing targeted mitigation strategies, this research not only aims to bolster technical and operational safety but also addresses the socio-economic and environmental factors that heighten the sector's susceptibility. The conclusion advocates for the ongoing refinement of safety measures, underlining the importance of vigilance, evaluation, and adaptability in overcoming the complexities of the risk landscape in Nigeria's oil and gas sector.